Α-Synuclein – Regulator of Exocytosis, Endocytosis, or Both?. Issue 7 (July 2017) - Lautenschläger, Janin; Kaminski, Clemens F.; Kaminski Schierle, Gabriele S.
Abstract : α-Synuclein is known as a presynaptic protein that binds to small synaptic vesicles. Recent studies suggest that α-synuclein is not only attracted to these tiny and therewith highly curved membranes, but that in fact the sensing and regulation of membrane curvature is part of its physiological function. Moreover, recent studies have suggested that α-synuclein plays a role in the endocytosis of synaptic vesicles, and have provided support for a function of α-synuclein during exo- and endocytosis in which curvature sensing and membrane stabilization are crucial steps. This review aims to highlight recent research in the field and adds a new picture on the function of α-synuclein in maintaining synaptic homeostasis upon intense and repetitive neuronal activity. Trends: Membrane remodeling processes are crucial steps for the exo- and endocytosis of synaptic vesicles. From structure–function relationships, α-synuclein has been proposed to be a curvature sensing and regulating protein, thus proposing a role in mechanisms of exo- and endocytosis. A function in exocytosis has been suggested (i) via mediating SNARE-complex assembly, (ii) curvature stabilization, thus preventing premature fusion of vesicles, and (iii) in tethering of synaptic vesicles via lipid binding of α-synuclein with both its N- and a more C-terminal region. Latest studies indicate a function of α-synuclein in synaptic vesicle endocytosis. (i) A possible function in clathrin-mediated endocytosis has been proposed, but a function also seems likely in (ii) fast endocytotic pathways such as kiss-and-run, or in (iii) the recently discovered ultrafast endocytosis process.